Self-reported Evaluation of Psychosocial Effects of Fluorosis among Inhabitants Living in a Rural Fluorosis Epidemic Area in China: Psychosocial Effects of Dental Fluorosis - Si, Yan; Lin, Huan-cai; Wang, Zuo-min; Zhang, Bo-xue; Hou, Yu-bo; Gao, Xue-jun (North American Journal of Medicine and Science, 2009)
Objective: The purpose of this study was to investigate the psychosocial effects of fluorosis on the patients in the fluorosis epidemic area. Methods: In the rural fluorosis epidemic areas in Hebei province of China, 416 inhabitants were randomly selected to be examined using Dean’s Index (DI). Surface Index of Fluorosis (TSIF) was used in 178 recruited participants who were also involved in a psychosocial questionnaire investigation. Demographic information and six five-point subscales about “Attitude to Teeth”, “Index of Well-Being”, “Index of General Affect”, “Interaction Anxiousness Scale” (IAS), “Self-Esteem Scale” (SES) and “Impact on Behavior” were included in the questionnaire. SPSS12.0 software was used to analyze the data.